2017
DOI: 10.1038/srep46652
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating levels of the interferon-γ–induced chemokines are associated with disease activity and cutaneous manifestations in adult-onset Still’s disease

Abstract: C-X-C motif chemokine 9 (CXCL9), CXCL10, and CXCL11 are produced in response to interferon-γ (IFN-γ) and trigger inflammation with the accumulation of activated lymphocytes. It appears that these chemokines could play a role in the pathogenesis of adult-onset Still’s disease (AOSD). Therefore, we investigated the associations between the levels of these chemokine and clinical manifestations in patients with active AOSD. Serum levels of IFN-γ, CXCL9, CXCL10 and CXCL11 were determined using enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
(51 reference statements)
1
39
0
2
Order By: Relevance
“…Activated CD4+ T cells release high IFN‐γ levels; this cytokine enhances chemokine expression for leukocyte recruitment by facilitating their transfer through the endothelial layer, increases antigen presentation, and promotes Th1 differentiation, all of these functions are preponderant in the pathophysiology of RA. We observed a borderline significant increase in the IFN‐γ serum levels of RA patients in relation to CS, which is in agreement with previous studies …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Activated CD4+ T cells release high IFN‐γ levels; this cytokine enhances chemokine expression for leukocyte recruitment by facilitating their transfer through the endothelial layer, increases antigen presentation, and promotes Th1 differentiation, all of these functions are preponderant in the pathophysiology of RA. We observed a borderline significant increase in the IFN‐γ serum levels of RA patients in relation to CS, which is in agreement with previous studies …”
Section: Discussionsupporting
confidence: 93%
“…We observed a borderline significant increase in the IFN-γ serum levels of RA patients in relation to CS, which is in agreement with previous studies. 37,38 Respecting to 1858C>T genotype, we observed that in the RA group, the presence of the risk allele favors a significant decrease in IFN-γ but intriguingly, in CS it is associated with an increase in IFN-γ levels. In this respect, a group of researchers documented that after in vitro antigen stimulation, CD4 + T cells from healthy donors carriers of 1858 T risk allele produced significantly higher amounts of IFN-γ and TNF-α than subjects carrying wild-type allele.…”
Section: Ptpn22 1858 T Risk Allele Is Associated With Decreased Ifnmentioning
confidence: 76%
“…To investigate the soluble factors that may correlate with the onset of fever spike, we measured sCD163, CXCL9, CXCL10 and CXCL11 before and after the administration of E + B combined therapy at the time of onset of a fever spike. These soluble factors were reported to correlate with the AE of anti‐PD‐1 antibody 6,10 and with the spike of fever in patients with AOSD 5 . Serum sCD163, CXCL9, CXCL10 and CXCL11 were increased in all three cases in parallel with their fever spike, but not in another three patients who had been treated with immune checkpoint inhibitors previously but did not develop pyrexia by E + B combined therapy (Fig.…”
Section: Case Reportsmentioning
confidence: 84%
“…Spike of fever is a well‐known symptom in AOSD 5 . Recently, sCD163 and IFN‐γ‐induced chemokines (CXCL9, CXCL10 and CXCL11) have been reported to correlate with the onset of pyrexia in AOSD 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation